Formation of single-crystalline BaTiO3 nanorods from glycolate by tuning the supersaturation conditions. Issue 9 (1st May 2022) - Kovalenko, O.; Škapin, S.D.; Maček Kržmanc, M.; Vengust, D.; Spreitzer, M.; Kutnjak, Z.; Ragulya, A.
Abstract: We have studied peculiarities in the formation of single-crystalline barium titanate (BaTiO3 ) nanorods from a glycolate-mediated complex via a single-step hydrothermal process under different supersaturation (SR ) conditions. X-ray diffraction (XRD) showed the formation of pure BaTiO3 with an SR of above 19. The tetragonality for the BaTiO3 (c/a) reached 1.013 at SR  = 19–29 and dropped to 1.010 for SR  = 39. According to the transmission electron microscopy (TEM) and XRD analyses, the rod-shaped particles exhibited single crystallinity and crystal growth along the [001] plane. With scanning electron microscopy (SEM), the morphological evolution from a plate-shaped intermediate precursor (SR  = 6–9) to a rod-shaped product with an aspect ratio of 6–9 (SR  = 19–29), and to non-polar material with an irregular structure (SR  = 39), was observed. The negative slope, linear dependence of the particles' width and length on the supersaturation level in the range SR  = 19–39 was established for the first time. The replacement of the prevailing crystallization mechanism from in-situ topotactic transformation into dissolution-precipitation above SR  = 19 was observed. It was shown that with a simple regulation of the SR, the structural and morphological characteristics of the obtained BaTiO3 nanoparticle can be effectively tuned.